Exploring task completion times and text performance in pedestrians in single and dual-tasking: Comparative analysis of laboratory and outdoor environments. - Girgin, Nuray; Okudan, Begum; Çelebi, Sadık Emre; Dündar, Selim (Work, 2025)
Background: Increased cell phone use causes individuals to divide their attentional resources between dual tasks in daily life. It is emphasized that this divided attention negatively affects task performance and makes pedestrian cell phone use an increasing safety concern. There is a lack of research on how dual tasks involving cell phone use affect pedestrian movements in laboratory and real-world settings and the time saved by text messaging while walking. Objectıve: The main purpose of this study is to investigate how dual-tasking affects pedestrians by analyzing task completion time and texting performance, as well as investigating potential gender differences. Methods: 119 students were included in the study. Expanded-Timed Up and Go Test was applied as a single task 1. As a single task 2; text messaging was used on a mobile phone. Dual-task was defined as performing both tasks simultaneously. All evaluations were recorded both in the laboratory and outdoor environment. Results: Between all parameters, task completion times showed a significant difference in favor of dual-task in both environments (p ≤ 0.05). There was no significant difference in texting performance when comparing the results of two environments (p ≥ 0.05). Performing texting and walking tasks simultaneously resulted in approximately 43–45% time savings. Conclusıons: However, dual-task increases events such as falling or hitting other pedestrians. We recommend that pedestrians do not endanger their health and the health of other pedestrians to save more or less time.